Childhood Trauma and Family Dysfunction in Bá and Way’s The Umbrella Academy: Apocalypse Suite - Örling, Roosa (My University, 2025)
In my thesis, I analyze the parental neglect in Gerard Way and Gabriel Bá's The Umbrella Academy: Apocalypse Suite and its impact on the characters and the development of their superhero identity. I also discuss how these themes are portrayed through the medium of comics. My goal is to describe how mental violence and its consequences appear in the comic and how they are depicted through the cooperation of text and image. Bá and Way’s The Umbrella Academy: Apocalypse Suite is the first volume of The Umbrella Academy series. At the beginning of the story, scientist Sir Reginald Hargreeves adopts seven children who were born at the same moment, each to different mothers. Every child has their own superpowers and Hargreeves’s plan is to form a superhero team called “The Umbrella Academy” with them. However, he selfishly takes advantage of the children, and the effects of this neglect are still visible in the adulthood of The Umbrella Academy. I utilize previous research on the impact of upbringing and sibling relationships on child development to support my analysis. I also apply studies on the consequences of jealousy and parental favoritism to the development of an individual's identity. These mentioned themes are clearly visible in this comic, and I discuss these psychological phenomena through selected panels from the comic. My thesis also includes a section where I consider how the medium influences the storytelling. In this section, I use previous comic studies to support my analysis. Through these various perspectives I claim that The Umbrella Academy: Apocalypse Suite portrays heavy themes in a multidimensional way.
Keywords: comic, graphic novel, childhood, trauma, identity, superhero comics, psychology